Tribological behaviors of graphene and graphene oxide as water-based lubricant additives for magnesium alloy cold rolling - XIE Hong-mei; JIANG Bin; DAI Jia-hong; TANG Chang-ping; LI Quan; PAN Fu-sheng (Cailiao gongcheng, 2019)
The tribological properties of garaphene and graphene oxide (GO) as water based additives were investigated for AZ31 Magnesium alloy cold rolling. The morphology and composition of surfaces were characterized by field emission scanning electron microscopy(FESEM) and Raman spectrum. The lubricating mechanism of graphene and graphene oxide(GO) as water-based additives was explored. The results indicate that the best tribological response of the magnesium alloy/steel pairs evaluated is obtained when GO and graphene at a concentration of 0.5%(mass fraction) is added to water. The friction coefficients of graphene nanofluids and GO nanofluids are 0.132 and 0.038, and the wear volumes are 23.1 mm3 and 2.59 mm3. Furthermore, the cold-rolling tests show that the application of GO nanofluids leads to a significant reduction in the rolling force and an improvement in the surface quality of sheets. Under the same testing conditions, the lubricating performance of GO nanofluids are superior to graphene nanofluids, which attributes to the superior dispersion in the water and prominent wetting of the GO nanofluids on the magnesium alloy surface.